Avaliação dos sinais clínicos, parasitemia e alterações hematológicas e bioquímicas de bovinos experimentalmente infectados pelo Trypanosoma vivax - Fidelis Junior, Otavio Luiz [UNESP]; Sampaio, Paulo Henrique [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Marques, Luiz Carlos [UNESP]; Cadioli, Fabiano Antonio [UNESP] (FapUNIFESP (SciELO), 2016)
Infections by Trypanosoma vivax cause great losses to livestock in Africa and Central and South Americas. Outbreaks due this parasite have been occurred with increasing frequency in Brazil. Knowledge of changes caused by T. vivax during the course of this disease can be of great diagnostic value. Thus, clinical signs, parasitemia, hematologic and biochemical changes of cattle experimentally infected by this hemoparasite were evaluated. Two distinct phases were verified during the infection – an acute phase where circulating parasites were seen and then a chronic phase where fluctuations in parasitemia were detected including aparasitemic periods. A constant reduction in erythrocytes, hemoglobin and packed cell volume (PVC) were observed. White blood cells (WBC) showed pronounced changes such as severe neutropenia and lymphopenia during the acute phase of the illness. Decreases in cholesterol, albumin, aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and increases in glucose, globulin, protein, and alkaline phosphatase (ALP) were observed. The “Lins” isolate of T. vivax showed pathogenicity for cattle, and intense parasitemia was detected in the early stages of infection. Circulating parasites were detected for about two months. The most evident laboratory abnormalities were found in WBC parameters, including thrombocytopenia.
Evaluation of clinical signs, parasitemia, hematologic and biochemical changes in cattle experimentally infected with trypanosoma vivax
Keywords: Bovine; Complete blood count; Host-parasite relationship; Trypanosomiasis